Protective Effects of Necrostatin-1 against Concanavalin A-Induced Acute Hepatic Injury in Mice - Yingqun Zhou; Weiqi Dai; Chunlei Lin; Fan Wang; Lei He; Miao Shen; Ping Chen; Chenfen Wang; Jie Lu; Ling Xu; Xuanfu Xu; Chuanyong Guo (Mediators of Inflammation)
Objective. Necrostatin-1 (Nec-1) inhibits receptor-interacting protein 1 (RIP1) kinase and programmed necrosis. This study was designed to examine the protective effects and mechanisms of Nec-1 in concanavalin A- (ConA-) induced hepatitis in mice. Methods. C57BL/6 mice were exposed to ConA via tail vein injection and injected intraperitoneally with Nec-1 or vehicle. Levels of serum liver enzymes and histopathology were determined. Levels of inflammatory cytokines with ConA-induced hepatitis were determined with real-time polymerase chain reaction (real-time PCR). The expression of TNF-α, RIP1, and LC3 was detected with immunohistochemical staining. The expression of TNF-α, IFN-γ, IL2, IL6, caspase 3, RIP1, beclin-1, and LC3 protein was assessed by immunofluorescence and western blotting. Autophagosomes were observed with transmission electron microscopy (TEM). Results. Amelioration in liver functions and histopathological changes and the suppression of inflammatory cytokine production were observed in Nec-1-injected mice. Western blotting analysis showed that the expression of TNF-α, IFN-γ, IL2, IL6, and RIP1 was significantly reduced in the Nec-1-injected mice, which was confirmed by immunofluorescence and immunohistochemistry. Autophagosome formation was significantly reduced by Nec-1 treatment, as the expression of beclin-1 and LC3, determined with immunofluorescence and western blotting. Conclusion. These results demonstrate that Nec-1 prevents ConA-induced liver injury via RIP1-related and autophagy-related pathways.